Vascular plant diversity of the high mountains of Fereydunshahr, Central Zagros, Iran - Mohsen Yaselyani; Ali Bagheri; Hojjatollah Saeidi; Jalil Noroozi (Vegetation Classification and Survey (VCS))
Questions: The mountains of Fereydunshahr County are one of the centers of plant endemism within the Zagros, however, its flora and vegetation remain relatively understudied. In this study we undertook research on the plant species diversity of the subalpine and alpine zones of this area, their life forms, chorology, and vegetation types. Study area: Mountains of Fereydunshahr County, Central Zagros, West Iran. Methods: Plant specimens were collected during the growing seasons of 2018 to 2020. A complete species list was prepared including their life forms, chorotypes, elevation range, and major vegetation types. Results: A total of 308 vascular plant species have been identified belonging to 185 genera and 47 families. The largest plant families recorded during the study are Asteraceae with 44 species, Fabaceae 32, Brassicaceae 29, and Lamiaceae 27. At genus level Astragalus with 23 species is the richest. Hemicryptophyte with 162 (53%) species is the major life form. Most of the species are Irano-Turanian elements (52%). A total of 57 species (19%) are endemic to Iran and 23 species (7%) are endemic to Zagros. Most species belong to the montane-subalpine zone (33%), followed by subalpine (20%), montane (15%), lowland-montane (10%), alpine (9%), and lowland-subalpine (5%). In the alpine zone a high proportion of the species are endemic, while the montane zone has a very low proportion of endemics. From the identified species, 24% belong to subalpine and alpine thorn-cushion grasslands, 19% to montane steppe shrublands, 5% to subalpine tall-umbelliferous vegetation types, 5% to wetlands, and 5% to chasmophyte vegetation. Conclusions: The area has a rich flora, but at the same time is under high pressure from anthropogenic activities, especially a very high level of overgrazing. The region is not a protected area, therefore, establishment of a protected area and efficient conservation planning for the region is highly recommended. Taxonomic reference: Flora of Iran (Assadi et al. 1989–2021) and, for families not yet covered in the previous source, Flora Iranica (Rechinger 1963–2015). Abbreviations: ES = Euro-Siberian; IT = Irano-Turanian; M = Mediterranean; SS = Saharo-Sindian.